Novel battery system based on dual-additive electrolyte system containing 1,2,6-oxodithiane-2,2,6,6-tetraoxide
A dual-additive electrolyte system with ODTO and either FEC or VC enhances lithium-ion battery performance and longevity by optimizing additive interactions, addressing the inefficiencies of multiple-additive systems and reducing costs.
Patent Information
- Application Number
- JP2024160817
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-08-07
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion battery systems face challenges in achieving optimal performance and longevity due to the lack of understanding of additive interactions, leading to unpredictable composition blends and increased costs with multiple additives, with dual-additive systems often underperforming compared to four-additive systems.
A dual-additive electrolyte system comprising 1,2,6-oxodithian-2,2,6,6-tetraoxide (ODTO) combined with either fluoroethylene carbonate (FEC) or vinylene carbonate (VC) and lithium bis(fluorosulfonyl)imide (LiPO2F2), paired with lithium nickel manganese cobalt oxide (NMC) positive electrodes and graphite negative electrodes, in organic solvents, to enhance battery performance and reduce costs.
The dual-additive system improves cycle life and reduces gas production, maintaining high charge transfer efficiency and capacity retention, extending battery lifespan and reducing costs compared to traditional systems.
Smart Images

Figure 2024178275000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to rechargeable battery systems, and more particularly to rechargeable lithium-ion battery systems. The synthesis of such a system, including a working electrolyte additive and an electrode, to improve the properties of the system. Related to learning. [Background technology]
[0002] Rechargeable batteries are used in electric vehicles and grid storage (e.g., as back-up power during power outages). An essential component of storage energy systems (for power generation, as part of microgrids, etc.) Depending on the application, a storage energy system requires different characteristics. Battery system chemistries must make trade-offs to create systems suited to their applications. For example, in automotive applications, especially electric vehicle applications, rapid charging and discharging is required. The ability to charge quickly is a key characteristic of the system. Electric vehicle owners want to accelerate quickly in traffic. There may be cases where it is necessary to discharge the system quickly, which requires the ability to discharge the system quickly. However, rapid charging and discharging places demands on the system, and the system components must also be designed to withstand such motion. The thermal conductivity may need to be selected to provide sufficient longevity under operating conditions.
[0003] Electrolyte additives are operative and can improve the life and For example, Non-Patent Document 1 lists five unique publications: The electrolyte additives not included in the test are compared with electrolyte systems that contain no additives or only one additive. In another study, described in US Pat. No. 5,933,663, the cycle life of the 100-kV 100-mAh battery was increased by 100%. As reported in the literature, the focus is on improving the performance of electrolyte systems containing three or four additives. However, researchers have generally found that the electrolyte and the specific positive and negative electrodes work synergistically. They do not understand the interactions between the different additives that allow them to work together. Therefore, the composition of the additive blend for a particular system is often based on trial and error and must be determined in advance. It's impossible to predict.
[0004] Previous research has focused on combining lithium-ion battery systems for grid or automotive use. We have identified a dual-additive electrolyte system that can produce a robust system with sufficient properties for use in As discussed in US Pat. No. 5,993,563, the two-additive system studied (e.g., 2% VC+1% allyl methanesulfonate and 2% PES+1% TTSPi) are usually three types and the performance was inferior to that of four additive electrolyte systems (see, for example, Table 1 of Patent Document 1). and Table 2.) Patent Document 1 discloses a method for producing a robust lithium-ion battery system. To achieve this, a third compound, often tris(-tris), is added at a concentration of 0.25% to 3% by weight. Tris(trimethylsilyl)-phosphate (TTSP) or tris(trimethylsilyl)- It is disclosed that a phosphite (TTSPi) was necessary (for example, Patent Document 1 (See paragraph 72 of the same document.) However, it can be expensive and difficult to produce Li Since it is difficult to include additives in ion batteries, more simple batteries, including those with fewer additives, are being developed. There is a need for pure yet effective electrolytes. Summary of the Invention [Means for solving the problem]
[0005] This disclosure provides a method for the production of a battery that can be used in a variety of energy storage applications, such as vehicle and grid storage. This includes a novel battery system that requires less working electrolyte additives. More specifically, this The disclosure improves the performance and lifespan of Li-ion batteries while relying on more additives. This disclosure also includes a dual additive electrolyte system that reduces the cost of other systems currently in use. In conjunction with the dual additive electrolyte system presented, an effective cathode and and a negative electrode.
[0006] Combined with 1,2,6-oxodithiane-2,2,6,6-tetraoxide (ODTO) A working additive electrolyte system containing vinylene carbonate (VC) is disclosed. ODTO has the following formula (I): TIFF2024178275000002.tif44111
[0007] Fluoroethylene carbonate (FEC) combined with ODTO and Combined LiPO 2 F 2 (here called LFO) is also disclosed. A system including at least two combinations of FO and VC and ODTO is also disclosed.
[0008] Because VC and FEC provide similar improvements (and are believed to function similarly), Therefore, the mixture of VC and FEC can be considered as a single effective electrolyte. The dual-acting additive electrolyte system disclosed is VC and FEC combined with ODTO. The larger battery system (which includes the electrolyte, electrolyte solvent, positive and negative electrodes) When used as part of a vehicle and grid, these dual acting additive electrolyte systems In addition, LFO produces desirable properties for storage and energy applications, including fuel cell applications. It acts effectively as an additive and is further enhanced by LFO in combination with FEC and / or VC. Additive systems can be made that can be improved.
[0009] More specifically, a lithium nickel manganese cobalt oxide (NMC) positive electrode and a graphite negative electrode. a lithium salt dissolved in an organic or non-aqueous solvent, which may include methyl acetate (MA); The two additives can form a battery system with desirable properties for various applications. The electrolyte solvent may be any of the following solvents, either alone or in combination: ethylene Carbonate (EC), Ethyl methyl carbonate (EMC), Methyl acetate, Propylene Carbonate, dimethyl carbonate, diethyl carbonate, another carbonate solvent ( (cyclic or acyclic), another organic solvent, and / or another non-aqueous solvent. The solvent may have a higher viscosity than the additive. Solvents are typically present in concentrations greater than 6% by weight. (mixture of VC and ODTO, FEC and ODTO, LFO and ODTO, VC and FEC and ODTO, or other combinations) to develop battery systems with desirable characteristics for various applications. The positive electrode is made of aluminum oxide (Al 2 O 3 ), titanium dioxide (Ti O 2 ), or another coating material. For convenience, the anode may be made from natural graphite, but depending on the pricing structure, certain examples may require So, synthetic graphite is cheaper than natural graphite.
[0010] The disclosure herein demonstrates the symbiotic nature of the two-additive electrolyte system and selected electrodes. This is supported by experimental data. An exemplary battery system includes two additives (e.g. , FEC, LFO or VC, ODTO), graphite anode (naturally occurring graphite or synthetic graphite ), NMC positive electrode, lithium electrolyte (e.g., chemical composition LiPF 6 Six fu lithium fluoride phosphate), and organic or non-aqueous solvents. In a further embodiment, the first additive comprises at least two of VC, LFO, and FEC. It's a combination.
[0011] An exemplary embodiment of this application comprises a lithium salt, a non-aqueous solvent, and vinylene carbonate. , LiPO 2 F 2 (LFO), fluoroethylene carbonate, or any combination thereof A first working additive selected from the group consisting of a compound represented by the following formula (I): The second working form of 1,2,6-oxodithiane-2,2,6,6-tetraoxide with TIFF2024178275000003.tif44111 and a mixture including an additive.
[0012] In another exemplary embodiment, the concentration of the first actuation type additive is 0.25% by weight to 6% by weight. The range is.
[0013] In another exemplary embodiment, the concentration of the second actuation type additive is 0.25% by weight to 5% by weight. The range is.
[0014] In another exemplary embodiment, the concentration of the first actuating additive is 2% by weight (VC or FEC). % (in the case of LFO) and 1 wt. % (in the case of LFO), and the concentration of the second working additive is 1 wt. do.
[0015] In another exemplary embodiment, the first working additive is fluoroethylene carbonate. do.
[0016] In another exemplary embodiment, the first working additive is vinylene carbonate.
[0017] In another exemplary embodiment, the first working additive is LiPO 2 F 2 It is.
[0018] In another exemplary embodiment, the non-aqueous solvent is a carbonate solvent.
[0019] In another exemplary embodiment, the non-aqueous solvent is ethylene carbonate and ethyl methyl and at least one selected from the group consisting of carboxylic acids, carboxylic acids, and carbonates.
[0020] In another exemplary embodiment, the electrolyte further comprises a second non-aqueous solvent.
[0021] Another exemplary embodiment of the present application is a cathode, a cathode, and a lithium-ion battery dissolved in a first non-aqueous solvent. Lithium ion, fluoroethylene carbonate, LiPO 2 F 2 and Vinyllenker a first working additive selected from a carbonate or any combination thereof, and a compound represented by the following formula ( I) The second working form of 1,2,6-oxodithiane-2,2,6,6-tetraoxide with TIFF2024178275000004.tif44111 and a non-aqueous electrolyte containing the additive mixture.
[0022] In another exemplary embodiment, the volume of gas produced in a lithium ion battery is determined by a first This is comparable to the amount of gas produced in a lithium-ion battery containing only the active additive.
[0023] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 200 cycles between 3.0V and 4.3V, the initial capacity is maintained at 95%.
[0024] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 300 cycles between 3.0V and 4.3V, the initial capacity is maintained at 95%.
[0025] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 400 cycles between 3.0V and 4.3V, the initial capacity is maintained at 95%.
[0026] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 500 cycles between 3.0V and 4.3V, the initial capacity is maintained at 95%.
[0027] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 600 cycles between 3.0V and 4.3V, the initial capacity is maintained at 95%.
[0028] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 700 cycles between 3.0V and 4.3V, the initial capacity is maintained at 95%.
[0029] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 800 cycles at 3.0V to 4.3V, the initial capacity is maintained at 95%.
[0030] In another exemplary embodiment, the lithium ion battery is charged at a charge rate of C / 3CCCV at 40° C. After 900 cycles at 3.0V to 4.3V, the initial capacity is maintained at 95%.
[0031] Another exemplary embodiment of the present application is a rechargeable battery, a drive motor, a gearbox, and a power supply. and an electric vehicle equipped with the battery system described herein. [Brief description of the drawings]
[0032] [Figure 1] FIG. 1 is a schematic diagram of a vehicle equipped with a storage battery system.
[0033] [Diagram 2] FIG. 1 is a schematic diagram of an exemplary battery storage system.
[0034] [Diagram 3] FIG. 1 is a schematic diagram of a lithium ion battery cell system.
[0035] [Figure 4A-4B] 1 shows the passivation effect of various electrolyte compositions in different types of cells. [Fig. 4C-4D] 1 shows the passivation effect of various electrolyte compositions in different types of cells. [Figure 4E] 1 shows the passivation effect of various electrolyte compositions in different types of cells.
[0036] FIG. 4A shows the relationship between ethylene carbonate (EC): ethyl methyl carbonate (EMC) (vs. (Reference), and 2%VC, 1%ODTO, 3%ODTO, 5%ODTO, 2%VC+1%OD TO, 2%FEC+1%ODTO, and 1%LFO(LiPO 2 F 2 ) + 1% ODTO Uncoated NMC532 / person containing electrolyte with EC:EMC Passivation effect by showing dQ / dV vs. V during formation cycle of graphite cells is illustrated.
[0037] FIG. 4B shows the relationship between ethylene carbonate (EC):ethyl methyl carbonate (EMC) (vs. (Reference), and 2%VC, 1%ODTO, 3%ODTO, 5%ODTO, 2%VC+1%OD EC:EMC including TO, 2%FEC+1%ODTO, and 1%LFO+1%ODTO Formation cycling of coated NMC532 / artificial graphite cells containing electrolytes with 4 illustrates the passivation effect by showing dQ / dV vs. V in
[0038] Figure 4C shows the results of 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, and 2 %FEC+1%ODTO, 1%LFO+1%ODTO, and 2%VC. Al 2 O 3 d during the formation cycle of coated NMC622 / artificial graphite cells Illustrates the passivation effect by showing Q / dV vs. V.
[0039] FIG. 4D shows the relationship between ethylene carbonate (EC):ethyl methyl carbonate (EMC) (vs. (Reference), and 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, 2% EC:EMC includes FEC+1%ODTO, 1%LFO+1%ODTO, and 2%VC A polycrystalline coating of aluminum, fluorine and oxygen (AFO) containing an electrolyte having dQ / dV versus formation cycle of NMC622 / artificial graphite cells coated with acrylic resins By showing V, the passivation effect is illustrated.
[0040] FIG. 4E shows the results of electrochemical analysis of electrodes containing 2% VC, 2% VC+1% ODTO, and 2% VC+3% ODTO. To show dQ / dV vs. V during formation cycling of electrolyte-containing lithium-ion battery cells This explains the passivation effect caused by this.
[0041] [Figure 5A-5B] Electrochemical Impedance Spectroscopy (EIS) spectra of different types of cells with various electrolyte compositions. [Fig. 5C-5D] Electrochemical Impedance Spectroscopy (EIS) spectra of different types of cells with various electrolyte compositions. [Figure 5E] Electrochemical Impedance Spectroscopy (EIS) spectra of different types of cells with various electrolyte compositions.
[0042] FIG. 5A shows a cell with an uncoated NMC532 cathode and a synthetic graphite anode. Within 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, 2% FEC +1% ODTO, 1% LFO+1% ODTO, 2% VC, 2% FEC, and 1% LFO 1 shows EIS spectra of different electrolyte systems containing ZnO.
[0043] FIG. 5B shows one cell with a coated NMC532 positive electrode and a synthetic graphite negative electrode. %ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1% ODTO, 1%LFO+1%ODTO, 1%LFO+1%ODTO+1%VC, 1%LF O+1%ODTO+1%FEC, 1%LFO+1%ODTO+1%TTSPi, 2%VC 13A-13C are EIS spectra of different electrolyte systems containing 0.1% ZnO, 2% FEC, and 1% LFO.
[0044] FIG. 5C shows the Al 2 O 3 Equipped with a coated NMC622 positive electrode and an artificial graphite negative electrode 1%ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%F in cells Different frequency bands including EC+1%ODTO, 1%LFO+1%ODTO, 2%VC, and 2%FEC. 4 shows EIS spectra of the electrolyte system.
[0045] FIG. 5D shows a cell with an AFO-coated NMC622 cathode and a synthetic graphite anode. Within 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, 2% FEC Different voltages include +1% ODTO, 1% LFO +1% ODTO, 2% VC, and 2% FEC. 1 is an EIS spectrum of the solution system.
[0046] FIG. 5E shows the results of 2% VC, 2% VC+1% ODTO, and 2% 13 shows EIS spectra of different electrolyte systems containing FEC+3% ODTO.
[0047] [Figure 6A] 1 illustrates the charge transfer resistance (Rct) of different types of cells with various electrolyte compositions measured after formation cycling. [Figure 6B] 1 illustrates the charge transfer resistance (Rct) of different types of cells with various electrolyte compositions measured after formation cycling. [Figure 6C] 1 illustrates the charge transfer resistance (Rct) of different types of cells with various electrolyte compositions measured after formation cycling. [Figure 6D] 1 illustrates the charge transfer resistance (Rct) of different types of cells with various electrolyte compositions measured after formation cycling. [Figure 6E] 1 illustrates the charge transfer resistance (Rct) of different types of cells with various electrolyte compositions measured after formation cycling.
[0048] FIG. 6A shows a cell with an uncoated NMC532 cathode and a synthetic graphite anode. Within 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, 2% FEC +1% ODTO, 1% LFO+1% ODTO, 2% VC, 2% FEC, and 1% LFO R of different electrolyte systems including ct is illustrated.
[0049] FIG. 6B shows one cell with a coated NMC532 positive electrode and a synthetic graphite negative electrode. %ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1% Different frequencies including ODTO, 1%LFO+1%ODTO, 2%VC, 2%FEC, and 1%LFO. R of electrolyte system ct is illustrated.
[0050] FIG. 6C shows the Al 2 O 3 Equipped with a coated NMC622 positive electrode and an artificial graphite negative electrode 1%ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%F in cells Different frequency bands including EC+1%ODTO, 1%LFO+1%ODTO, 2%VC, and 2%FEC. R of electrolyte system ct is illustrated.
[0051] FIG. 6D shows one cell with a coated NMC622 positive electrode and a synthetic graphite negative electrode. %ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1% Different electrolyte systems including ODTO, 1% LFO + 1% ODTO, 2% VC and 2% FEC were used. System R ct is illustrated.
[0052] FIG. 6E shows a lithium-ion battery with a coated NMC622 cathode and a synthetic graphite anode. Includes 2%VC, 2%VC+1%ODTO, and 2%VC+3%ODTO in the on-cell battery. R of different electrolyte systemsct is illustrated.
[0053] [Figure 7A] The experimental data of the volume of formation gas produced during cell formation for different electrolyte systems is summarized. [Figure 7B] The experimental data of the volume of formation gas produced during cell formation for different electrolyte systems is summarized. [Figure 7C] The experimental data of the volume of formation gas produced during cell formation for different electrolyte systems is summarized. [Figure 7D] The experimental data of the volume of formation gas produced during cell formation for different electrolyte systems is summarized. [Figure 7E] The experimental data of the volume of formation gas produced during cell formation for different electrolyte systems is summarized.
[0054] FIG. 7A shows a cell with an uncoated NMC532 positive electrode and a synthetic graphite negative electrode. Within 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, 2% FEC +1% ODTO, 1% LFO+1% ODTO, 2% VC, 2% FEC, and 1% LFO Summarizing experimental data on the volume of formation gas produced during cell formation for electrolyte systems containing This is the plot.
[0055] FIG. 7B shows one cell with a coated NMC532 positive electrode and a synthetic graphite negative electrode. %ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1% Includes ODTO, 1%LFO+1%ODTO, 2%VC, 2%FEC, and 1%LFO. A summary of experimental data on the volume of reaction gas produced during cell formation for the electrolyte system. It is a lot.
[0056] FIG. 7C shows the Al 2 O 3Equipped with a coated NMC622 positive electrode and an artificial graphite negative electrode 1%ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%F in cells Electrolytic containing EC+1%ODTO, 1%LFO+1%ODTO, 2%VC, and 2%FEC A program to summarize experimental data on the volume of conversion gas produced during cell conversion for a sintered system. It is.
[0057] FIG. 7D shows a cell with an AFO-coated NMC622 cathode and a synthetic graphite anode. Within 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO, 2% FEC +1% ODTO, 1% LFO +1% ODTO, 2% VC, and 2% FEC. A plot summarizing experimental data on the volume of formation gas produced during cell formation for the stem. It is.
[0058] FIG. 7E shows the results of the comparison of 2% VC, 2% VC+1% ODTO, and The formation gas generated during cell formation for the electrolyte system containing 2% VC + 3% ODTO 1 is a plot summarizing experimental data on the capacitance of
[0059] [Figure 8A-8B] 1 illustrates voltage versus time during high temperature storage for different NMC622 / synthetic graphite cells with various electrolyte systems.
[0060] FIG. 8A shows the Al 2 O 3 Equipped with a coated NMC622 positive electrode and an artificial graphite negative electrode 1%ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%F in cells High temperature analysis of different electrolyte systems including EC+1%ODTO and 1%LFO+1%ODTO Graph showing voltage versus time during storage.
[0061] FIG. 8B shows one cell with a coated NMC622 positive electrode and a synthetic graphite negative electrode. %ODTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1% The electric potential of different electrolyte systems containing ODTO and 1% LFO + 1% ODTO during high temperature storage Pressure versus time is illustrated.
[0062] [Figure 9] FIG. 9 illustrates the parasitic heat flow in experiments involving various electrolyte additive systems in a lithium-ion battery cell.
[0063] [Figure 10A] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10B] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10C] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10D] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10E]Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10F] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10G] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10H] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10I] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10J] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10K] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Fig. 10L-10M]Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10N] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10O] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10P] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10Q] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10R] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10S] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10T]Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10U] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10V] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown. [Figure 10W] Experimental data including discharge capacity, normalized discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) collected during cycling experiments for various electrolyte systems are shown.
[0064] 10A to 10I show the results of a test using a coated NMC532 positive electrode and an artificial graphite negative electrode. Discharge capacities, normalized to 100, were collected during cycling experiments of various additive electrolyte systems. Discharge capacity (or fade rate), charge endpoint capacity, coulombic efficiency, and ΔV( The experimental data is plotted, including the difference between the average charge voltage and the average discharge voltage.
[0065] 10J to 10K show the results of the uncoated NMC532 positive electrode and the synthetic graphite negative electrode. during cycling and ultra-precise cycling experiments of various electrolyte systems using The collected discharge capacity, normalized discharge capacity (or fade rate), and charge endpoint capacity The experimental data including the charge capacity, coulombic efficiency, and ΔV (difference between the average charge voltage and the average discharge voltage) are shown in Fig. Show.
[0066] 10L to 10R show Al 2 O 3 Coated and AFO Coated Cycling experiments using NMC622 positive and synthetic graphite negative electrodes in various electrolyte systems Discharge capacity, normalized discharge capacity (or fade rate), and charge endpoints collected during Experimental data including capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) is illustrated.
[0067] Figure 10S shows the cycling of various electrolyte systems using a lithium-ion battery cell. The discharge capacity, normalized discharge capacity (or fade rate), and ΔV(average The experimental data including the difference between the average charge voltage and the average discharge voltage is shown.
[0068] Figure 10T shows the cycling of various electrolyte systems using a lithium-ion battery cell. The discharge capacity, normalized discharge capacity (or fade rate), and ΔV(average The experimental data including the difference between the average charge voltage and the average discharge voltage is shown.
[0069] Figure 10U shows the cycling of various electrolyte systems using a lithium-ion battery cell. Discharge capacity, normalized discharge capacity (or fade rate), and charge endpoints were collected during the experiment. Experimental data including inlet capacity, coulombic efficiency, and ΔV (difference between average charge voltage and average discharge voltage) The data is illustrated.
[0070] FIG. 10V shows the results for coated and uncoated NMC532 positive electrodes and Artificial graphite anode and Al2 O 3 Coated and AFO coated NM During cycling experiments using C622 cathodes and synthetic graphite anodes in various electrolyte systems The collected discharge capacity, normalized discharge capacity (or fade rate), and ΔV (average charge voltage The experimental data is plotted, including the difference between the average discharge voltage and the average discharge voltage.
[0071] FIG. 10W shows coated and uncoated NMC532 cathodes and Artificial graphite anode and Al 2 O 3 Coated and AFO coated NM During cycling experiments using C622 cathodes and synthetic graphite anodes in various electrolyte systems The collected discharge capacity, normalized discharge capacity (or fade rate), and ΔV (average charge voltage The experimental data is plotted, including the difference between the average discharge voltage and the average discharge voltage.
[0072] [Figure 11] Illustrates coulomb inefficiency per hour versus cycle number, partial charge endpoint capacity shift per hour versus cycle number, and partial capacity fade per hour versus cycle number for electrolyte systems containing 1% ODTO, 3% ODTO, 5% ODTO, 2% VC+1% ODTO, 2% FEC+1% ODTO, 1% LFO+1% ODTO, 2% VC, and 2% FEC using an uncoated NMC532 cathode and synthetic graphite anode cycling from 3.0 V to 4.3 V.
[0073] [Figure 12]Illustrates coulomb inefficiency per hour versus cycle number, partial charge endpoint capacity shift per hour versus cycle number, and partial capacity fade per hour versus cycle number for electrolyte systems containing 1% ODTO, 3% ODTO, 5% ODTO, 2% VC+1% ODTO, 2% FEC+1% ODTO, 1% LFO+1% ODTO, 2% VC, 2% FEC, and 1% LFO using coated NMC532 cathodes and synthetic graphite anodes cycled from 3.0 V to 4.3 V.
[0074] [Figure 13] Illustrates coulomb inefficiency per hour versus cycle number, partial charge endpoint capacity shift per hour versus cycle number, and partial capacity fade per hour versus cycle number for electrolyte systems containing 1% ODTO, 3% ODTO, 5% ODTO, 2% VC+1% ODTO, 2% FEC+1% ODTO, 1% LFO+1% ODTO, 2% VC, and 2% FEC using an Al2O3 coated NMC622A cathode and synthetic graphite anode cycled from 3.0 V to 4.3 V.
[0075] [Figure 14] Illustrates coulomb inefficiency per hour versus cycle number, partial charge endpoint capacity shift per hour versus cycle number, and partial capacity fade per hour versus cycle number for electrolyte systems containing 1% ODTO, 3% ODTO, 5% ODTO, 2% VC+1% ODTO, 2% FEC+1% ODTO, 1% LFO+1% ODTO, 2% VC, and 2% FEC using AFO coated NMC622B cathode and synthetic graphite anode cycling from 3.0 V to 4.3 V.
[0076] [Figure 15] 1 illustrates the average parasitic heat flow per cycle in experiments involving various electrolyte additive systems in lithium-ion battery cells.
[0077] [Figure 16]1 illustrates the change in voltage and gas capacity over time for experiments involving various electrolyte additive systems in a lithium-ion battery cell.
[0078] [Figure 17] 1 illustrates the parasitic heat flow in experiments involving various electrolyte additive systems in a lithium-ion battery cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0079] FIG. 1 shows the basic components of a battery-powered electric vehicle (EV) 100. The electric vehicle 100 includes at least one drive motor (traction motor) 102A and / or 10 2B, at least one gear coupled to the corresponding drive motor 102A and / or 102B a box 104A and / or 104B, a battery cell 106 and an electronic device 108 Generally, the battery cells 106 power the electronics of the electric vehicle 100 and the drive motor. 102A and / or 102B may be used to provide electrical power to propel the electric vehicle 100. Electric vehicle 100 may be combined with many other electric vehicles not described herein but known to those skilled in the art. The electric vehicle 100 of FIG. 1 is configured to have four wheels. Although shown in FIG. 1, different electric vehicles may have fewer or more than four wheels. Includes motorcycles, aircraft, trucks, boats, and train engines, among other types of vehicles. Different types of electric vehicles 100 may incorporate the inventive concepts described herein, including: Certain components made using embodiments of the present disclosure may be used in the vehicle 100. It is possible.
[0080] FIG. 2 illustrates a schematic diagram of an exemplary energy storage system 200 showing various components. The energy storage system 200 generally comprises at least a base 202 and four side walls 204. The modular housing includes four modules (only two shown in the figure). The battery housing is generally electrically isolated from the battery cells 206 contained therein. The physical separation is achieved by the electrical insulation layer, which is a layer of insulating material as the module housing. By choice, any combination thereof, or otherwise, may occur. 02 is an electrical insulating layer on a metal sheet, or a material such as polypropylene, polyurethane, or polyvinyl chloride. Non-conductive / electrically insulating such as nylon, another plastic, a non-conductive composite or insulating carbon fiber The sidewalls 204 may also include an insulating layer, or may be made of polypropylene. , polyurethane, polyvinyl chloride, other plastics, non-conductive composites or insulating carbon The interconnect may be formed from a non-conductive or electrically insulating material such as a fiber. The layer 230 can be disposed over the battery cells 206 and the top plate 210 can be The top plate 210 may be a single plate or may be a multi-layer plate. The plate may be formed from a number of plates.
[0081] Each battery cell 106 and 206 includes an electrolyte containing lithium ions, a positive electrode, In most cases, the battery is a lithium-ion battery cell with a negative electrode and a positive electrode. A schematic diagram of a lithium ion battery 300 is shown. Lithium ions 350 are distributed throughout the electrolyte 320 within a container 360. The container 360 may be part of a battery cell. The lithium ions 350 are The separator 370 separates the negative electrode from the positive electrode. The circuit 310 connects the negative terminal and the positive terminal.
[0082] New research by the inventors reveals novel ion exchange refractories for use in grid and electric vehicle applications Suitable electrolyte and battery systems were identified. These systems consisted of 1,2,6-oxoditidine. Vinylene carbonate combined with 2,2,6,6-tetraoxyethylene (ODTO) LiPO combined with VC, ODTO 2 F 2 and fluo in combination with ODTO A dual additive electrolyte system was developed by combining electrodes with a solvent containing fluoroethylene carbonate (FEC). These two-additive electrolyte systems are based on LNi x Mn y Co z O 2 (Commonly abbreviated as NMC or NMCxyz, where x, y and z are nickel, manganese, Lithium nickel manganese cobalt oxide with a composition of 1000:1 (molar ratio of 1000:1, ... In a particular embodiment, the positive electrode is made of NMC111, In certain embodiments, the covalent bond is formed from NMC532, NMC811, or NMC622. Single crystals resulting in electrodes with micrometer-sized areas of continuous crystal lattice (or coarse grains) The NMC532 cathode, formed from micrometer-sized particles of crystalline It has been shown to be particularly robust due to its high thermal conductivity and processing conditions, which make it easier to fabricate than conventional materials. and the particle size is larger than when using the processing conditions.
[0083] Typical processing conditions result in nanometer-sized particles being converted into larger micrometer-sized particles. This resulted in an NMC electrode packed into agglomerates of nanometer-sized particles, and grain boundaries were created on the nanometer scale. Grain boundaries are defects that tend to degrade desirable properties (e.g. electrical properties). In general, it is desirable to reduce the number of coarse particles and increase their size because of defects. Larger domains can be created on the micrometer size scale, making NM C The number of grain boundaries in the electrode is reduced, improving electrical properties. The improved properties lead to a more robust battery system. In certain embodiments, other NMC electrodes are processed to provide larger dots. Main size (micrometer size scale and above), e.g. NMC111, NMC Create 811, NMC622, or another NMC compound to create a more robust system It is possible.
[0084] The positive electrode is aluminum oxide (Al 2 O 3 ), titanium dioxide (TiO 2 ), or another code The positive electrode may be coated with a material such as a coating material. The coating material of the positive electrode may be used to prevent parasitic reactions, or another phenomenon that may degrade cells containing coated materials, such as This is advantageous because it may help reduce interfacial phenomena in the anode. It may be made from graphite, or other materials.
[0085] The electrolyte is ethylene carbonate, ethyl methyl carbonate, methyl acetate, propylene Carbonate, dimethyl carbonate, diethyl carbonate, other carbonate solvents (cyclic or acyclic), another organic solvent, and / or another non-aqueous solvent. A lithium salt (LiPF 6 The solvent may be added The experimental data are presented in EC:E Electrolytes containing MC:DMC at 25:5:70 by volume (with or without methyl acetate (MA)) Although these were produced using solvents, these solvents were not compatible with other carbonate solvents, especially other non-carbonate solvents. This is just an example for an aqueous solvent. To understand the effect of additives and electrodes, Solvents were used in the experiments to control the systems tested. Thus, the electrolyte system was Propylene carbonate, ethylene carbonate, dimethyl carbonate, ethyl methyl Carbonates, diethyl carbonate, other carbonate solvents (cyclic or acyclic), other Organic solvents and / or other non-aqueous solvents, including carbonate solvents and / or other non-carbonate solvents. A carbonate solvent can be used. The solvent is present in a higher concentration than the additive, usually greater than 5% by weight. Or is present at more than 6% by weight.
[0086] In the two-additive mixture of FEC + ODTO, the concentration of FEC is preferably 0.5 wt.% to 6% by weight, and the concentration of ODTO is preferably 0.25% to 5% by weight. In the two-additive mixture of +ODTO, the concentration of VC is preferably 0.5% to 6% by weight. The concentration of LFO+ODT is preferably 0.25% by weight to 5% by weight. In the two-additive mixture of O, the concentration of LFO is preferably 0.5% to 1.5% by weight. The concentration of ODTO is preferably 0.25% by weight to 5% by weight.
[0087] These particular new battery systems are being developed for energy storage applications and also for automotive applications (electric vehicles). In this application, the charging and discharging speed, as well as the rapid charging and discharging The life span when discharging is important.
[0088] Pre-experiment configuration Although the battery system itself may be packaged separately according to the present disclosure, the experimental setup includes: Typically, a machine-made "closed cell" is used to create a two-additive electrolytic Systematically develop a battery system that includes a specific material for use in the cathode and anode. All percentages referred to within this disclosure are by weight unless otherwise specified. Those skilled in the art will appreciate that the types of additives used and the concentrations employed will determine the most desirable Improved properties, as well as other components used in the lithium-ion batteries produced It will be understood that these are dependent on the design and will be apparent from this disclosure.
[0089] Sealed Battery Cell The NMC / graphite sealed cell used in the experimental setup contained 1M LiP in a solvent with additives. F 6 The electrolyte contained 1M LiPF in 30% EC and 70% EMC. 6 From The concentrations of the electrolyte components can be modified to include MA and / or DMC. To this electrolyte was added the additive component at the weight percent specified.
[0090] The sealed battery cells used in the experiment were EC, EMC, and D with a volume ratio of 25:5:70. 1.2M LiPF added to MC 6 The electrolyte contained an electrolyte solvent consisting of Additive ingredients were added at the weight percentages specified.
[0091] Closed NMC / graphite cells are filled with coarse micrometer-sized N particles unless otherwise specified. Cathode made of MC532 (sometimes called single crystal NMC532) and synthetic graphite To test the specific battery system, anodes made of NMC532 (Magnetron) were used. (coarse particles smaller than NMC622) and other positive Anodes and cathodes (containing natural graphite) were used.
[0092] Before filling the electrolyte, the sealed cells were cut open below the heat seal and heated at 100°C for 12 hours. Residual moisture was removed by vacuum drying. The cells were then immediately loaded and vacuum sealed. After transferring to an argon-filled glove box, the electrolyte was filled. The vacuum seal was performed.
[0093] After sealing, the sealed cell was placed in a temperature box at 40.0 + / - 0.1℃ and tested at 1.5V for 24 hours. The cell was then held for 10 minutes to allow wetting to complete, after which the closed cell was subjected to a conversion process. Unless otherwise stated, the formation process for NMC / graphite cells is 4. The experiment consisted of charging a sealed cell to 2 V and discharging it to 3.8 V. C / x is the initial charge on the cell. If there is a fixed capacity, the time it takes to charge or discharge the cell at the selected current is x hours. For example, C / 20 indicates that it takes 20 hours to charge or discharge. Afterwards, the cell was moved to a glove box, cut open to release the generated gas, and then re- The device was vacuum sealed once and appropriate experiments were carried out.
[0094] The formation process of the battery cells for cycling and storage experiments was carried out by heating the sealed cells at 40°C. Charge the cell at C / 2 for 1 hour, store the cell at 60°C for 22 hours, and store the cell at 40°C. The battery was charged to 4.2V at C / 2 and discharged to 3.8V. The cell was then moved to a glove box, cut open to release the gases, and then reassembled. The appropriate experiments were carried out under vacuum.
[0095] Formation process of battery cells for charge profile and in-situ gas capacity measurement experiments The cell was connected to an in-situ gas measurement instrument and then heated at 40°C for C / 2 The test consisted of charging to 4.2V at 0°C and discharging to 3.8V at C / 20 at 40°C. .
[0096] Passivation effect The passivation effect of various electrolyte compositions in different types of cells is shown in Fig. 4A-B. As can be seen from the data in Figures 4A-4E, ODTO was able to detect the oxidative stress in five different types of tissues. The same passivation effect is observed in the first and second cells (Fig. 4). In Figure 4A-B), the uncoated NMC532 cathode (Figure 4A) and the synthetic graphite The cell with the electrodes, as well as the coated NMC532 positive electrode (FIG. 4B) and the synthetic graphite positive electrode (FIG. 4C). Ethylene carbonate (EC); ethyl methyl carbonate (E MC) (control), 2% VC, 1% ODTO, 3% ODTO, 5% ODTO, 2% VC+1 %ODTO, 2%FEC+1%ODTO, and 1%LFO+1%ODTO passivation In the third and fourth cells (FIGS. 4C and 4D), the Al 2 O 3 Coat The cell with the AFO-coated NMC622 / artificial graphite electrode (Fig. 4C) and the AFO-coated NMC622 / artificial graphite electrode (Fig. 4D). 2% VC, 1% LFO + 1% ODTO, 2 in a cell with C622 electrodes (Figure 4D). %FEC+1%ODTO, 2%VC+1%ODTO, 1%ODTO, 3%ODTO and 5 % ODTO shows the passivation effect. And in the fifth cell (Figure 4E), EC: EMC: DMC, 2%VC, 2%VC+1%ODTO, 2%VC+3%ODTO passivation The peak at approximately 2.3 V is the OD in the presence of 1% ODTO. The effect of 1% ODTO additive is 2 O 3 Coated NMC622 positive, AFO coated NMC622 positive 4C-4E for the respective data of the electrodes found in the battery cell. As demonstrated by the work, the results are independent of the type of positive electrode used.
[0097] Cell Impedance The dual additive electrolyte system and novel battery system disclosed herein have low cell immunity. The cell impedance reduces the energy efficiency of the cell, It is desirable to minimize cell impedance. Conversely, low impedance The possible charging rates are higher and energy efficient.
[0098] Cell impedance was measured using electrochemical impedance spectroscopy (EIS). Charge or charge the cells to 3.80V before moving them to a 10.0+ / -0.1°C temperature box. The AC impedance spectrum was recorded at 10.0 + / - 0.1°C with a signal of 10 mV. The amplitudes ranged from 100kHz to 10mHz and were collected at 10 points per 10 minutes. The charge transfer resistance (R ct ) was calculated and plotted.
[0099] In certain embodiments, a two-additive electrolyte system is used in which the concentration of each additive is about 0.25% to 6%. The system forms part of the battery system. 1% ODTO, 3% ODTO, 5% ODTO in cells with NMC532 positive and synthetic graphite negative electrodes ODTO, 2%VC+1%ODTO, 2%FEC+1%ODTO, 1%LFO+1%OD TO, 2% VC, 2% FEC and 1% LFO (Figure 5A); coated NMC53 2 1% ODTO, 3% ODTO, 5% ODTO in cells with positive and negative graphite electrodes, 2%VC+1%ODTO, 2%FEC+1%ODTO, 1%LFO+1%ODTO, 1% LFO+1%ODTO+1%VC, 1%LFO+1%ODTO+1%FEC, 1%LFO + 1% ODTO + 1% TTSPi, 2% VC, 2% FEC and 1% LFO (Figure 5B); 1% O in cells with l2O3-coated NMC622 positive electrodes and synthetic graphite negative electrodes DTO, 3%ODTO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1%OD TO, 1% LFO + 1% ODTO, 2% VC and 2% FEC (Figure 5C); AFO coating 1% ODTO, 3% ODTO in cells with NMC622 positive and synthetic graphite negative electrodes TO, 5%ODTO, 2%VC+1%ODTO, 2%FEC+1%ODTO, 1%LFO +1% ODTO, 2% VC and 2% FEC (Figure 5D); and another lithium-ion battery cell 2% VC, 2% VC + 1% ODTO, 2% FEC + 3% ODTO in the same channel (Figure 5E). Experimental data from cell charge transfer impedance experiments of a dual additive electrolyte system are presented. A synthetic graphite negative electrode was used in each of these electrochemical cells.
[0100] In addition, the charge transfer impedance (R ct ) was examined for these cells. Figure 6 As shown in the data in Figures 6A to 6E, the cell charge transfer impedance is Compared with electrolytes containing O or 5% ODTO, 1% ODTO alone or 2% FEC, 2% It is reduced by 1% ODTO combined with VC or 1% LFO. Therefore, these new The dual additive electrolyte system significantly improved the charge transfer impedance by including ODTO. There is no sacrificing ability.
[0101] Gas volume measurement The chemical conversion process is used to convert the cells into energy storage or grid storage in vehicles such as electric vehicles. During formation, the cells are precisely controlled and The electrodes and the electrodes are subjected to a charge-discharge cycle to prepare them for their intended use. The purpose is to activate the electrolyte. Gas is produced during the formation process. (Depending on the cell A sufficient amount of gas is generated (depending on the specific tolerances and packaging of the cell allowed) In some cases, it may be necessary to release the gas after the conversion process and before use in the application. This usually requires the additional steps of breaking the seal and then resealing it. This is common in many battery systems, but if possible, choose a system that produces less gas. It is desirable to eliminate these steps by selecting
[0102] The gas capacity experiment was carried out as follows: Ex-situ (static) gas measurements were used to measure the gas content during formation. The gas evolution during cycling was measured. The measurements were carried out using Archimedes' principle. The cell was suspended from a balance while submerged in the body. The change in front and back is directly related to the change in volume due to the change in buoyancy. It is suspended in a fluid of density ρ. The change in cell mass, Δm, is related to the change in cell volume, Δv, as Δv=-Δm / ρ. The gases generated during the intermediate and high potential holding periods were analyzed by the method described by Aiken et al. (CPAi ken, J.Xia, David Yaohui Wang, D.A. Stevens, S.Trussler and JRDahn,J.Electrochem.So c. 2014 volume 161, A1548-A1554) The measurements were performed using an in-situ gas measurement device.
[0103] In certain embodiments, a two-additive electrolyte system is used in which the concentration of each additive is about 0.25% to 6%. The system forms part of the battery system. 1% ODTO, 3% ODTO, 5% ODTO in cells with NMC532 positive and synthetic graphite negative electrodes ODTO, 2%VC+1%ODTO, 2%FEC+1%ODTO, 1%LFO+1%OD TO, 2% VC, 2% FEC and 1% LFO (Figure 7A); coated NMC53 2 1% ODTO, 3% ODTO, 5% ODTO in cells with positive and negative graphite electrodes, 2%VC+1%ODTO, 2%FEC+1%ODTO, 1%LFO+1%ODTO, 2% VC, 2% FEC and 1% LFO (Figure 7B); Al2O3-coated NMC62 2 1% ODTO, 3% ODTO, 5% ODTO in cells with positive and negative graphite electrodes, 2%VC+1%ODTO, 2%FEC+1%ODTO, 1%LFO+1%ODTO, 2% VC and 2% FEC (Figure 7C); coated NMC622 positive electrode and synthetic graphite negative electrode 1% ODTO, 3% ODTO, 5% ODTO, 2% VC + 1% ODTO in cells with , 2%FEC+1%ODTO, 1%LFO+1%ODTO, 2%VC and 2%FEC (Fig. 7D); 2%VC, 2%VC+1%ODTO and 2%V in another lithium-ion battery cell Results of gas generation experiments in a two-additive electrolyte system consisting of C + 3% ODTO (Figure 7E). The results are shown in Table 1. Each of these electrochemical cells used an artificial graphite anode. In each case, the amount of gas produced was measured according to the procedure described above. In the cell with 1% ODTO or 1% LFO + 1% ODTO shown in E, However, gas production was significantly lower in the 2% VC + 1% ODTO and 2% F It was significantly reduced in the EC+1% ODTO cells.
[0104] Energy storage experiment After formation, the cell was discharged twice to 3 V and charged to 4.4 V at a current corresponding to C / 10. The cell was then held at 4.4 V for 24 hours and then transferred to a storage box at 60°C. The open circuit voltage was automatically recorded every 6 hours for 500 hours. It was found that the cell incorporating 2VC+1ODTO exhibited the lowest self-discharge under these conditions. This indicates that:
[0105] Ultra-Precision Cycling To study the effectiveness of the disclosed battery system including the working electrolyte additive and electrodes, Ultrahigh precision cycling (UHPC) The standard UHPC procedure was performed at 40°C using a current corresponding to C / 20. Cycle the cell from 3.0V to 4.3V for 15 cycles to generate data. In the case of Coulombic efficiency, the shift in Coulombic efficiency, charging end point capacity, and other parameters to an accuracy of 30 ppm. Details of the C procedure are given in TM Bond, JC Bu, which is incorporated herein in its entirety. rns,DAStevens,HMDahn,and JRDahn,Jo Urnal of the Electrochemical Society,160 ,A521(2013).
[0106] Metrics measured and / or determined from UHPC measurements of particular interest include Coulomb efficiency rate, normalized coulombic efficiency, normalized charge end point capacity deviation, normalized discharge capacity (i.e. The coulombic efficiency is a function of the discharge capacity (Q d )of Charge capacity of previous cycle (Q c The coulombic efficiency of a Li-ion cell is It tracks the parasitic reactions occurring at the cathode and anode, including contributions from both the anode and cathode. The higher the CE value, the This indicates that the deterioration of the electrolyte in the cell is small. The coulomb efficiency per hour (CIE / h) is , is the normalized coulombic efficiency (per hour), where the coulombic efficiency is defined as 1-CE CIE / h is calculated by taking 1-CE and dividing by the cycle time over which CE is measured. The movement (or deviation) of the charging endpoint capacity is due to the parasitic reactions occurring at the positive electrode. Track the mass loss of the cathode material, if any. Less movement is better, and the electrolyte acid Normalized discharge capacity, or fade rate, is another important It is a metric, and a lower fade rate is more desirable and typically translates into a longer battery system life. ΔV is calculated as the difference between the average charge voltage and the average discharge voltage. The change in ΔV is It is closely related to the growth of polarization, and the change in ΔV becomes smaller as cycling occurs. UHPC measurements allow for more accurate tracking of metrics and identify various degradation mechanisms. This is particularly suitable for comparing electrolyte compositions because it allows for a relatively rapid evaluation of
[0107] Here, 1%ODTO, 3%ODTO, 5%ODTO, 1%ODTO+2%VC, 1 %ODTO+2%FEC, 1%ODTO+1%LFO, 2%VC, 2%FEC, 2%VC , 20%MA+2%VC, 20%MA+2%VC+1%ODTO and 1%LFO are used. The UHPC experiments were carried out using five different cell cathode materials, including a coated Uncoated (Fig. 11) and coated (Fig. 12) NMC532 and Al 2 O 3 Coated NMC622 (Figure 13) and AFO coated NMC62 2 (Figure 14), as well as other lithium-ion battery cell active materials. The raw data for the coated NMC532 cells are shown in Figures 10D and 10E. The raw data for NMC532 cells without Al are shown in Figures 10J and 10K. 2 O 3 Coati The raw data for the coated NMC622 cells are shown in Figures 10O and 10P. The raw data for the NMC622 cell is shown in Figures 10Q and 10R. The raw data of the on battery cell is shown in Figure 10U.
[0108] In certain embodiments, a two-additive electrolyte system is used in which the concentration of each additive is about 0.25% to 6%. The battery system also includes the NMC111, NMC5 32, NMC811, NMC622, or other NMC compositions (NMCxyz) In certain embodiments, the positive electrode may comprise a micrometer-scale coarse-grained NMC. The cathodes made from 532 are due, in part, to the fact that the processing conditions produce a higher Cr content than normal processing conditions would produce. It has been shown to be particularly robust for producing large grain sizes.
[0109] Typical processing conditions result in nanometer-sized particles being converted into larger micrometer-sized particles. This resulted in an NMC electrode packed into agglomerates of nanometer-sized particles, and grain boundaries were created on the nanometer scale. Grain boundaries are defects that tend to degrade desirable properties (e.g. electrical properties). In general, it is desirable to reduce the number of coarse particles and increase their size because of defects. can create larger domains on the micrometer size scale, The number of grain boundaries in NMC electrodes is reduced, improving their electrical properties. The improved properties result in more robust electrical connections. In certain embodiments, other NMC electrodes are treated to form larger pond systems. Domain size (micrometer size scale or larger), e.g., NMC111, N Create MC811, NMC622, or another NMC compound to create a more robust system. It can be put out.
[0110] Long-term cycling The lifespan of a battery system is an important characteristic of the battery system. The rate of charging and discharging affects the lifespan. Long-term cycling experiments may affect resilience under expected operating conditions. It is useful for determining the aging of a battery system. The choice of system is important.
[0111] Embodiments of the present disclosure provide desirable long-term storage for a variety of applications, including grid and vehicle storage. Specifically, VC+ODTO, LFO+ODTO and FEC+O DTO's dual additive electrolyte system is designed to operate at rates that are typically lower than the charge and discharge rates typically found in grid storage applications. This is relevant for automotive applications (especially energy storage in electric vehicles), where the costs are higher than in the past.
[0112] For long-term cycling experiments, we typically used single crystal NMC532 and N MC622 was used as the positive electrode and artificial graphite was used as the negative electrode. Prior to this, the closed cells were subjected to a conversion process as described above for each cell type. After formation, the cells were cycled in a Neware charging system.
[0113] In some experiments, the cells were housed in a temperature-controlled box at 40°C + / - 0.2°C. 3 At the start of charging with .0V and a current of C / 3 (3 hour half cycle) Between the voltage step (4.2V or 4.3V) and the constant voltage step at the beginning of charging, the current is C / 2 The cells were cycled until the charge dropped below 0. Every 50 cycles, the cells underwent one complete charge at C / 20. The results of such an experiment on coated NMC532 are shown in Figure 10A. 10B, 10C, 10V(b) and 10W(b), NMC532 without Al is shown in Fig. 10V(a) and Fig. 10W(a). 2 O 3 Courting The NMC622 coated with AFO is shown in Figures 10L, 10V(c) and 10W(c). The NMC622 is shown in Figures 10M, 10N, 10V(d), and 10W(d). Another lithium-ion battery cell is shown in FIG. 10T(b).
[0114] In some experiments, the cells were housed in a temperature-controlled box at 55°C + / - 0.2°C. 3 At the start of charging with .0V and a current of C / 3 (3 hour half cycle) Between the voltage step (4.2V or 4.3V) and the constant voltage step at the beginning of charging, the current is C / 2 The cells were cycled until the charge dropped below 0. Every 50 cycles, the cells underwent one complete charge at C / 20. The results of such an experiment on coated NMC532 were as follows: 10F and 10G, and for other lithium ion battery cells, FIG. 10S and FIG. The results are shown in T(c).
[0115] In some experiments, the cells were housed in a temperature-controlled box at 20°C + / - 0.2°C. 3 At the start of charging with .0V and a current of C / 3 (3 hour half cycle) Between the voltage step (4.2V or 4.3V) and the constant voltage step at the beginning of charging, the current is C / 2 The cells were cycled until the charge dropped below 0. Every 50 cycles, the cells underwent one complete charge at C / 20. The results of such an experiment on coated NMC532 are shown in Figure 10. The results for the other lithium-ion battery cell are shown in Figure 10H, and the results for the other lithium-ion battery cell are shown in Figure 10T(a).
[0116] In some experiments, the cells were housed in a temperature-controlled box at 20°C + / - 0.2°C. 3 When charging starts with .0V and a current of 1C (1 hour to charge, 1 hour to discharge) ( top of charge) (4.2V or 4.3V) and the constant voltage step at the start of charging The cell was cycled between 0.5 and 1000 cycles until the current fell below C / 20. Every 50 cycles, the cell was cycled between 0.5 and 1000 cycles until the current fell below C / 20. The coated NMC532 underwent one complete cycle at 100 / 20. The results of this experiment are shown in FIG. 10I.
[0117] The experimental data were obtained for two-additive electrolyte systems (ODTO+FEC, ODTO+LFO, and DTD+VC) loses less capacity when cycling to 4.2V or 4.3V The polarization growth is also lower compared to single additive electrolyte systems with VC or FEC. and that cycling is similar to 2%VC+1%DTD and 1%LFO+2FEC. This shows that:
[0118] A study of the average parasitic heat flow per cycle (Figs. 15, 17 and 9) and the charging Further studies, including in-situ gas assessment during charge retention, have been performed with other lithium-ion batteries. I went to Ike Cell.
[0119] The gas capacity experiment was carried out as follows: Ex-situ (static) gas measurements were used to measure the gas content during formation. The gas evolution during cycling was measured. The measurements were carried out using Archimedes' principle. The cell was suspended from a balance while submerged in the body. The change in front and back is directly related to the change in volume due to the change in buoyancy. It is suspended in a fluid of density ρ. The change in cell mass, Δm, is related to the change in cell volume, Δv, as Δv=-Δm / ρ. The gases generated during the intermediate and high potential holding periods were analyzed by the method described by Aiken et al. (CPAi ken, J.Xia, David Yaohui Wang, D.A. Stevens, S.Trussler and JRDahn,J.Electrochem.So c. 2014 volume 161, A1548-A1554) The measurements were performed using an in-situ gas measurement device.
[0120] The results in Figure 16 show that the ODTO is able to withstand high voltages with and without 20% MA during charging / holding. It has been shown to be beneficial in suppressing gases in Microcalorimetry
[0121] Microcalorimetry measures the heat flow into a cell during operation. The heat flow into the cell can be determined in three different ways: Combination of effects: (1) Ohmic heating, (2) Entropy change due to Li insertion at the electrode. and (3) parasitic reactions (degradation of the electrolyte with additives at either electrode). The cells contain the same physical design with only the electrolyte differing, so the difference in heat flow is primarily due to However, Downie et al. l of the Electrochemical Society,161,A17 82-A1787(2014)) and Glazier et al. (Journal of the Electrochemical Society,164(4)A56 Parasitic heat flows are extracted from the total heat flow using the procedure developed by (7-A573(2017)). All of these references are incorporated herein in their entirety. Cells with less parasitic heat flow during cycling have a longer life. The performance can be observed by plotting the measured parasitic heat flow as a function of cell voltage. .
[0122] Microcalorimetry procedure: Connect two cells of each electrolyte to a Maccor charger and heat to 40.0 °C. on a TAMIII microcalorimeter (TA Instruments, stability + / - 0.00 The temperature was measured using a temperature sensor with a temperature sensor ... -0.5 μW. All information regarding calibration, cell connection, and operating procedures for microcalorimetry. All specifications and information have been published in previous publications (e.g., Downie et al. l, ECS Electrochemical Letters 2, A106-A10 9 (2013)) To ensure a properly formed and stable SEI, the cells are kept at 3.0V to 4.2V. Cycle 4 times at a C / 20 rate of 4.0 V and 3.7 mA (C / 100) The performance and parasitic heat flow in various voltage ranges were investigated by charging between different upper cutoffs of Each pair of cells performed nearly identically, so one set of heat flow data was collected for each electrolyte. Only present.
[0123] The 3.7mA cycling protocol was as follows: Charge to 14.0V, discharge to 3.9V, repeat Charge to 2.4.1V, discharge to 3.9V (repeated) Charge to 3.4.2V, discharge to 3.9V (repeated) 6. Charge to 4.0V, discharge to 3.9V (repeated)
[0124] The experimental data shown in Figs. 15, 17 and 9 are based on the electrolyte additives 2VC, 2VC+1O Other links include DTO, 2VC with 20% MA and 2VC+1ODTO with 20% MA. The test was performed on a lithium-ion battery cell at 3.9V to 4.2V. In this situation, the parasitic heat flow is reduced and the 1% ODTO Other lithium-ion battery cells, including This suggests that battery packs will last longer, potentially extending their lifespan to several years or miles of driving. It is important to
[0125] In certain embodiments, the positive electrode is NMC111, NMC532, NMC822, NMC6 22 and / or NMCxyz. In particular, the positive electrode made of single crystal NMC532 The pole is more polycrystalline and has a smaller grain size than other standard NMC materials. The grain size of 2 has been shown to be particularly robust, in part because of its larger grain size.
[0126] The foregoing disclosure is not intended to limit the present disclosure to the precise forms or particular fields of use disclosed. Therefore, whether or not expressly stated or implied herein, Nevertheless, various alternative embodiments and / or modifications to the present disclosure may be made in light of the present disclosure. Although the embodiments of the present disclosure have been described in this manner, those skilled in the art will be able to It will be understood that changes may be made in form and detail without departing from the scope of the present disclosure. It will be recognized that the present disclosure is limited only by the scope of the claims. References to additives in the specification generally refer to active agents, unless otherwise stated in this specification. Refers to additives.
[0127] In the foregoing specification, the present disclosure has been described with reference to specific embodiments. As will be appreciated by those skilled in the art, the various embodiments disclosed herein are intended to be illustrative, not restrictive, and are not intended to be limiting of the scope and spirit of the present disclosure. The present invention may be modified or embodied in various other ways without departing from the scope of the present invention. The above description should be considered as illustrative and various implementations of the disclosed battery system are within the scope of the present invention. It is intended to teach those skilled in the art how to make and use the morphology. It is to be understood that the forms of disclosure shown and described herein are to be taken as exemplary embodiments. It is to be understood that equivalent elements or materials may be used in conjunction with those typically illustrated and described herein. Moreover, certain features of the present disclosure are independent of the use of other features. any of which will be apparent to those of ordinary skill in the art after having the benefit of this description of the present disclosure. The term "including" is used to describe and claim this disclosure. "comprising," "incorporating," "incorporating" The expressions "comprising," "consisting of," "having," etc. shall be interpreted in an exclusive manner, i.e., with respect to any matters not expressly stated, There may also be a component or element. Reference to the singular is also to be construed as relating to the plural. References to "about" or "approximately" mean plus or minus 10%. Similarly, any reference to a percentage of an additive should be construed as plus or minus. is interpreted as meaning minus 10%.
[0128] Moreover, the various embodiments disclosed herein are intended to be illustrative and explanatory. and should not be construed as limiting the disclosure in any way. References (e.g., attached, pasted, joined, connected, etc.) are to aid the reader in understanding this disclosure. and is not intended to be used in any manner that would be construed as limiting the scope of the invention, particularly with respect to the location, orientation or use of the systems and / or methods disclosed herein. Therefore, binding references, if any, are to be interpreted broadly. Moreover, such joinder references do not necessarily infer that two elements are directly connected to each other. It is not something to measure.
[0129] Further, without limitation, terms such as "first," "second," "third," "primary," "main," " All absolute numbers, such as "secondary," "primary," or other conventional terms and / or absolute numbers, are used in this disclosure. The following is a list of the concepts and embodiments of the present invention that are intended to aid the reader in understanding the various elements, embodiments, variations and / or modifications of the present invention. The invention is to be taken as merely a separate entity and is not to be construed as limiting or exclusive of any particular element, embodiment, variation and / or modification. Any limitations on the order or priority of any elements, embodiments, variations and / or modifications to the above. It is not possible to set up
[0130] Also, one or more elements shown in the drawings / diagrams may be useful depending on the particular application. may also be implemented in a more separate or integrated manner, or even in certain cases It is understood that in some cases it may be deleted or disabled. [Prior art documents] [Patent documents]
[0131] [Patent Document 1] US Patent Application Publication No. 2017 / 0025706 [Non-patent literature]
[0132] [Non-Patent Document 1] JC Burns et al., Journal of the Electrochemical Society, 160, A1451 (2013)
Claims
1. A lithium salt; A non-aqueous solvent; Vinylene carbonate, LiPO 2 F 2 , fluoroethylene carbonate or their Any combination of a first working additive and a compound represented by the following formula (I): The second compound is 1,2,6-oxodithiane-2,2,6,6-tetraoxide having the formula A mixture including a dynamic additive; 1. A non-aqueous electrolyte for a lithium ion battery comprising:
2. 2. The method of claim 1, wherein the concentration of the first working additive is in the range of 0.25% to 6% by weight. The non-aqueous electrolyte according to claim 1.
3. 2. The method of claim 1, wherein the concentration of the second working additive is in the range of 0.25% to 5% by weight. The non-aqueous electrolyte according to claim 1.
4. The concentration of the first working type additive is at least 1% by weight, and the concentration of the second working type additive is at least 1% by weight.
2. The non-aqueous electrolyte of claim 1, wherein the concentration of is at least 1% by weight.
5. 5. The non-aqueous composition of claim 4, wherein the first working additive is fluoroethylene carbonate. Aqueous electrolyte.
6. 5. The non-aqueous electrolytic solution of claim 4, wherein the first working additive is vinylene carbonate. quality.
7. The first working additive is LiPO 2 F 2 5. The non-aqueous electrolyte of claim 4, wherein
8. The non-aqueous electrolyte of claim 1 , wherein the non-aqueous solvent is a carbonate solvent.
9. The non-aqueous solvent is selected from ethylene carbonate and ethyl methyl carbonate. The non-aqueous electrolyte of claim 8 , wherein the non-aqueous electrolyte is at least one of:
10. The non-aqueous electrolyte of claim 8 further comprising a second non-aqueous solvent.
11. 1. A lithium ion battery, A cathode; A positive electrode and A non-aqueous electrolyte comprising lithium ions dissolved in a first non-aqueous solvent and an additive mixture. The additive mixture comprises: Fluoroethylene carbonate, LiPO 2 F 2 , vinylene carbonate or the like and a first working additive, which is any combination of The following formula (I) The second compound is 1,2,6-oxodithiane-2,2,6,6-tetraoxide having the formula a non-aqueous electrolyte including a catalytic additive; A lithium-ion battery comprising:
12. 2. The method of claim 1, wherein the concentration of the first working additive is in the range of 0.25% to 6% by weight.
2. The lithium ion battery according to claim 1.
13. 2. The method of claim 1, wherein the concentration of the second working additive is in the range of 0.25% to 5% by weight.
2. The lithium ion battery according to claim 1.
14. The concentration of the first working type additive is at least 1% by weight, and the concentration of the second working type additive is at least 1% by weight.
12. The lithium ion battery of claim 11, wherein the concentration of is at least 1 wt.%.
15. 15. The method of claim 14, wherein the first working additive is fluoroethylene carbonate. Lithium-ion battery.
16. 15. The lithium salt of claim 14, wherein the first working additive is vinylene carbonate. Ion battery.
17. The first working additive is LiPO 2 F 2 The lithium ion according to claim 14, battery.
18. 12. The lithium ion battery of claim 11, wherein the non-aqueous solvent is a carbonate solvent.
19. The non-aqueous solvent is selected from ethylene carbonate and ethyl methyl carbonate. The lithium ion battery of claim 18.
20. 20. The lithium ion battery of claim 18, further comprising a second non-aqueous solvent.
21. The amount of gas produced in the lithium ion battery is greater than that in the lithium ion battery containing only the first working additive.
15. The lithium ion battery of claim 14, which is comparable in capacity to the gas produced by a lithium ion battery. Battery.
22. The lithium ion battery has a charge rate of 3.0V to 4.3V at 40°C and C / 3 CCCV.
22. The rechargeable battery of claim 21, having at least 95% retention of initial capacity after 200 cycles. Sium-ion battery.
23. The lithium ion battery is charged at 3.0V and 4.3V at a charge rate of C / 3 CCCV at 40°C.
22. The method of claim 21, wherein the capacity retention is at least 95% after 800 cycles between Lithium-ion battery.
24. An electric vehicle equipped with a rechargeable battery, A drive motor; The gearbox and Electronics and An electric vehicle comprising the lithium ion battery according to claim 11.
25. 2. The method of claim 1, wherein the concentration of the first working additive is in the range of 0.25% to 6% by weight.
5. The electric vehicle according to claim 4.
26. 2. The method of claim 1, wherein the concentration of the second active additive is in the range of 0.25% to 5% by weight.
5. The electric vehicle according to claim 4.
27. The concentration of the first working type additive is at least 1% by weight, and the concentration of the second working type additive is at least 1% by weight.
25. The electric vehicle of claim 24, wherein the concentration of is at least 1% by weight.
28. 28. The method of claim 27, wherein the first working additive is fluoroethylene carbonate. Electric car.
29. 28. The electric motor of claim 27, wherein the first working additive is vinylene carbonate. car.
30. The first working additive is LiPO 2 F 2 28. The electric vehicle of claim 27,
31. 25. The electric vehicle of claim 24, wherein the non-aqueous solvent is a carbonate solvent.
32. The non-aqueous solvent is selected from ethylene carbonate and ethyl methyl carbonate.
32. The electric vehicle of claim 31, wherein the at least one
33. 33. The battery of claim 32, wherein the lithium ion battery further comprises a second non-aqueous solvent. moving car.
34. The volume of gas produced in the battery system is greater than that of a battery system containing only the first working additive.
25. The electric vehicle of claim 24, wherein the volume of gas produced by the system is comparable to that of the gas produced by the electric vehicle.
35. The battery system is charged at 40° C. and C / 3 CCCV with a charge rate of 3.0 V to 4.3 V at 200 25. The electric auto battery of claim 24, having at least 95% retention of initial capacity after cycling. car.
36. The battery system is charged at 40° C. and C / 3 CCCV with a charge rate of 3.0 V to 4.3 V, for a total capacity of 800 V.
32. The electric motor of claim 31, having at least 95% retention of initial capacity after cycling. car.
Citation Information
Patent Citations
Secondary battery
JP2009038018A
Nonaqueous electrolyte secondary battery
JP2010153207A
Electrolyte and secondary battery
JP2010165542A
Nonaqueous electrolytic solution secondary battery
JP2010192326A
Secondary battery, electronic device, power tool, electric vehicle, and power storage system
JP2012199172A
